Large scaled analysis of hepatitis B virus (HBV) DNA integration in HBV related hepatocellular carcinomas. Issue 8 (11th July 2005) - Murakami, Y; Saigo, K; Takashima, H; Minami, M; Okanoue, T; Bréchot, C; Paterlini-Bréchot, P
Abstract : Background and aims: Hepatitis B virus (HBV) DNA integration into or close to cellular genes is frequently detected in HBV positive hepatocellular carcinomas (HCC). We have previously shown that viral integration can lead to aberrant target gene transcription. In this study, we attempted to investigate common pathways to hepatocarcinogenesis. Methods: By using a modified Alu-polymerase chain reaction approach, we analysed 50 HCCs along with 10 previously published cases. Results: Sixty eight cellular flanking sequences (seven repetitive or unidentified sequences, 42 cellular genes, and 19 sequences potentially coding for unknown proteins) were obtained. Fifteen cancer related genes and 25 cellular genes were identified. HBV integration recurrently targeted the human telomerase reverse transcriptase gene (three cases) and genes belonging to distinct pathways: calcium signalling related genes, 60s ribosomal protein encoding genes, and platelet derived growth factor and mixed lineage leukaemia encoding genes. Two tumour suppressor genes and five genes involved in the control of apoptosis were also found at the integration site. The viral insertion site was distributed over all chromosomes except 13, X, and Y. Conclusions: In 61/68 (89.7%) cases, HBV DNA was integrated into cellular genes potentially providing cell growth advantage. Identification of recurrent viral integration sites into genes of the same family allows recognition of common cell signalling pathways activated in hepatocarcinogenesis.